Feasibility of Environmentally Friendly and Conventional Shallot Farming in Kulon Progo Regency - Kamardiani Diah Rina; Afrilia Shelvyana; Innayah Raudhatul; Budiarto (E3S Web of Conferences, 2024)
Shallots cultivated by farmers in the Daerah Istimewa Yogyakarta, especially Bantul Regency and Kulon Progo Regency, have implemented environmentally friendly farming, apart from conventional farming. This research aims to analyze the costs, income, profits and feasibility of environmentally friendly and conventional shallot farming in Kulon Progo Regency. This research was conducted in Srikayangan Village, which is a center for shallots in Kulon Progo Regency, both environmentally friendly and conventional. Simple random sampling was used by drawing lots using Microsoft Excel, then 30 environmentally friendly farmers and 26 conventional farmers were chosen. Data analysis used costs, revenue and profits by testing using the independent sample t-test in the SPSS application. Quantitative descriptive analysis to analyze feasibility of farming using R/C. The research results showed the production costs of conventional shallot farming are lower than environmentally friendly shallot but not significantly. However, the income and profit of conventional shallot farming is higher than environmentally friendly farming. This is due to crop failure in environmentally friendly shallot production. Environmentally friendly and conventional shallot farming were feasible with an R/C value of more than one. Although conventional shallot farming was more profitable, it occurred due to crop failure on environmentally friendly shallots farming.